Eye yoga exercises to reduce eye fatigue syndrome during online learning - Wilandika, Angga; Fatmawati, Ariani; Padhli, Fikri Nurul; Lusiani, Eli; Amalia, Maya (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2024)
Background: Eye fatigue syndrome increases as students use computers and smartphones during online learning. Interventions to reduce the eye fatigue syndrome and avoid the severity of its symptoms need to be performed with appropriate and easy-to-practice techniques.Objective: This study aims to determine effects of eye yoga exercises on eye fatigue syndrome in students during online learning. Methods: This study applied one group pretest-post-test design involving 30 students from Universitas ‘Aisyiyah Bandung, West Java Province, Indonesia. Its samples were collected by using a proportional stratified random sampling. The eye yoga exercises were practiced four times for one week and had to begin 30 minutes after the end of online learning. The eye fatigue syndrome was measured using the Computer Vision Syndrome Questionnaire (CVS-Q). The difference in the intervention effect was calculated by using the Wilcoxon Signed-Rank Test. Results: This study revealed that the yoga eye exercises significantly affected the eye fatigue syndrome (Z= -4.636; p-value < 0.05). The average eye fatigue score decreased; the eye fatigue score before the intervention was 14.40 ± 9.17, and it decreased to 9.17 ± 4.88 after the eye yoga exercise intervention was given.Conclusion: Eye yoga exercises can reduce the level of eye fatigue syndrome in students who are learning by using electronic devices. The exercises can be performed independently to reduce this syndrome when working with a computer or smartphone. This intervention can be a standard for preventing the syndrome in educational institutions by incorporating eye yoga exercises after learning activities, particularly in online learning.